New Canadian guideline provides evidence-based approach to non-occupational HIV prophylaxis. Issue 1 (20th November 2018) - O'Donnell, Shannon; Tan, Darrell H. S.; Hull, Mark W.
Abstract: The incidence of HIV infections in Canada has increased yearly since 2014. New cases of HIV have resulted almost exclusively from non-occupational exposures, including sexual contact and needle sharing. Appropriate HIV post-exposure prophylaxis is under-prescribed to patients who present to the emergency department after a high-risk exposure. In November of 2017, a Canadian guideline on HIV pre-exposure prophylaxis (PrEP) and non-occupational post-exposure prophylaxis (nPEP) was published. The guideline presents a standardized, evidence-based approach to assessing risk for HIV transmission and prescribing HIV prophylaxis. This summary highlights the key points from the guideline that are relevant to the practice of emergency medicine in Canada. Résumé: L'incidence des infections à VIH au Canada croît sans cesse chaque année depuis 2014. La hausse du nombre de nouveaux cas d'infection s'explique presque exclusivement par des expositions non professionnelles au virus, attribuables par exemple à des contacts sexuels ou au partage de seringues. Toutefois, les médecins ne prescrivent pas suffisamment de mesures prophylactiques appropriées de postexposition aux patients qui consultent au service des urgences après une exposition à haut risque au VIH. Une nouvelle ligne directrice canadienne sur la prophylaxie préexposition au VIH et sur la prophylaxie postexposition non professionnelle a été publiée en novembre 2017. Elle porte sur une démarche uniforme et fondée sur des données probantes pour évaluer le risque de transmission du VIH et pour prescrire des mesures prophylactiques anti-VIH. Sera présenté dans l'article un résumé des principaux éléments de la ligne directrice, qui trouvent application dans la pratique de la médecine d'urgence au Canada.